2012
DOI: 10.1128/aem.06212-11
|View full text |Cite
|
Sign up to set email alerts
|

Differential Protection of Cry1Fa Toxin against Spodoptera frugiperda Larval Gut Proteases by Cadherin Orthologs Correlates with Increased Synergism

Abstract: The Cry proteins produced by Bacillus thuringiensis (Bt) are the most widely used biopesticides effective against a range of crop pests and disease vectors. Like chemical pesticides, development of resistance is the primary threat to the long-term efficacy of Bt toxins. Recently discovered cadherin-based Bt Cry synergists showed the potential to augment resistance management by improving efficacy of Cry toxins. However, the mode of action of Bt Cry synergists is thus far unclear. Here we elucidate the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 54 publications
2
20
0
1
Order By: Relevance
“…Similarly, the SfCad fragment from S. frugiperda increased Cry1Fa toxicity to S. frugiperda larvae more than did the MsBtR1 fragment from M. sexta (57). Our data support the hypothesis proposed previously by Chen et al (22) and Peng et al (54) that the binding of cadherin peptide to Cry toxin is a prerequisite for the peptide's enhancement effect.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similarly, the SfCad fragment from S. frugiperda increased Cry1Fa toxicity to S. frugiperda larvae more than did the MsBtR1 fragment from M. sexta (57). Our data support the hypothesis proposed previously by Chen et al (22) and Peng et al (54) that the binding of cadherin peptide to Cry toxin is a prerequisite for the peptide's enhancement effect.…”
Section: Discussionsupporting
confidence: 82%
“…However, the soluble HaBtR fragment reduces Cry1Ac insecticidal toxicity (27), whereas the HaBtR fragment produced in the inclusion body enhances Cry1Ac insecticidal toxicity (54) to H. armigera larvae. These results suggested that other synergistic mechanisms (for example, soluble versus inclusion body) rather than the cadherin binding affinity may also influence the synergistic ability of cadherin peptides (57). Our enhancement results of rSeCad1bp and rHaBtRp to different Cry toxins in S. exigua and H. armigera provide an excellent system to comparatively address the mechanisms.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This was demonstrated for native populations of S. frugiperda in Mexico, Brazil, and Colombia, which showed differences in susceptibility to Bt strains due to high genetic variability among populations; a fact that results in groups lacking receptors for certain Bt proteins and, thus, are insensitive to insecticidal proteins (Monnerat et al 2006). Aranda et al (1996) demonstrated in trials with S. frugiperda that insufficient and (or) a weak link of the insecticidal protein in the midgut binding sites can also affect the susceptibility to Cry1Ac, which can also be related to the inactivation of the insecticidal protein by proteases (Rahman et al 2012). …”
Section: Lepidopteran Pestsmentioning
confidence: 99%
“…Adicionalmente, uma quantidade insuficiente e/ou fraca ligação da proteína inseticida nos sítios de ligação do intestino médio também pode afetar a suscetibilidade a Cry1Ac, isso foi demonstrado para S. frugiperda a Cry1Ab (ARANDA et al, 1996) e S. exigua a Cry1C (de MAAGD et al, 2000), também pode estar relacionada com a inativação da proteína inseticida por proteases (MIRANDA; ZAMUDIO; BRAVO, 2001;RAHMAN et al, 2012 …”
Section: Spodoptera Cosmioides Spodoptera Eridania Spodoptera Frugiperdaunclassified